Comparison of environmental pollution and social cost analyses in different drying technologies. (7th September 2020) - Motevali, Ali; Jafari, Hassan; Molkabadi, Esmaeili Zakipour; Zhu, Songming; Koloor, Reza Tabatabaee; Taghizadeh-Alisaraei, Ahmad
Four different widely used dryers (i.e., recirculation, fluidised-bed, hybrid hot-air/infrared, and hybrid microwave/hot-air dryers) were used to analyse the gas emissions from different drying processes of Aloe vera. According to the results, the highest and lowest actual specific energy consumption were 306.977 and 3.182 kWh/kgwater reported for fluidised-bed and hybrid microwave/hot-air dryers, respectively. Given the energy consumption of different dryers, the highest CO2, SO2 and NOx emission levels were 314.651, 4.689 and 0.827 kg/kgwater for the steam power plant, 337.06, 1.195 and 1.778 kg/kgwater for the gas turbine plant, and 190.940, 0.714 and 1.161 kg/kgwater for the combined-cycle power plant. The lowest energy consumption was reported for drying with the microwave/hot-air dryer at 60°C, airflow velocity of 0.3 m/s and power level of 300 W. The highest and lowest social costs for the microwave/hot-air dryer under the said conditions were 0.12 and 0.08 USD for evaporating 1 kg water, which belonged to gas turbine and combined-cycle plants, respectively. According to the results, the lowest emission level was observed in the combined-cycle power plant when burning natural gas.